2015
DOI: 10.1007/s00246-015-1127-3
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethyl-l-Arginine is a Biomarker for Disease Stage and Follow-Up of Pulmonary Hypertension Associated with Congenital Heart Disease

Abstract: This study investigated the clinical value of plasma asymmetrical dimethyl-L-arginine (ADMA) level in the diagnosis, staging, and treatment response in congenital heart disease (CHD) patients with pulmonary arterial hypertension (PAH). This was a single-center prospective observational study in 80 CHD patients. Plasma ADMA levels were measured by enzyme-linked immunosorbent assay. Plasma ADMA levels were significantly increased in CHD patients with PAH compared with CHD patients without PAH (P < 0.01) and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…This comes in agreement with results of other investigators. 7,9 Moreover, there was a significant positive correlation between asymmetric dimethyl-L-arginine levels and right ventricular diameter. This is in agreement with the study by Sanli et al 8 As higher asymmetric dimethyl-L-arginine levels were found with higher pulmonary pressure, and pulmonary vascular resistance that were reflected on increased the right ventricular diameter.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This comes in agreement with results of other investigators. 7,9 Moreover, there was a significant positive correlation between asymmetric dimethyl-L-arginine levels and right ventricular diameter. This is in agreement with the study by Sanli et al 8 As higher asymmetric dimethyl-L-arginine levels were found with higher pulmonary pressure, and pulmonary vascular resistance that were reflected on increased the right ventricular diameter.…”
Section: Discussionmentioning
confidence: 95%
“…This agreed with the results of previous studies. [7][8][9][10][11] We have found that plasma asymmetric dimethyl-L-arginine levels were significantly reduced after treatment with sildenafil for 6 months. The reduced asymmetric dimethyl-L-arginine levels were accompanied by significant reduction in pulmonary pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fang et al reported that plasma ADMA levels are markedly related with pulmonary arterial pressure, right ventricular pressure, pulmonary vascular resistance, and mixed venous oxygen saturation. Thus, plasma ADMA level is effective in follow‐up evaluation in CHD patients with PH . Endothelial damage is correlated with an imbalance between endothelium‐derived vasoactive mediators which favour a vasoconstrictive and proliferative phenotype that presents the basis for the development of pulmonary vascular remodelling and the eventual progression to PH when additional elements, such as hypoxia and emphysema, concur…”
Section: Discussionmentioning
confidence: 99%